PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN MEDIA STIK KATA UNTUK MENINGKATKAN KETERAMPILAN MENYUSUN KALIMAT BAGI SISWA BERKESULITAN BELAJAR KELAS I SD - MULYANI, SRI (Jurnal Pendidikan Khusus, 2015)
Abstract : Learning disabilities students are students who have neurological disorders that are manifested in the inability written and oral expression, one result of students learning disabilities is arranging sentences. The aim of this study is to improve the learning outcomes arranging sentences skills through cooperative learning Type Think Pair Share with Word Sticks Media in first grade students Wedi Inclusion Elementary School. The approach of this study is qualitative descriptive with a class action methods. The class action methods draft (Kemmis & Taggart, 2008) is used and implemented in the second cycle of the procedure: (a) planning; (b) carry out the action; c) observations; d) evaluation and reflection. The data were collected with a non-participant observation technique. The analysis of data using flow techniques. The findings of the student activities in arranging declatarive sentence, introgative sentece and imperative sentence outcomes construct a sentence in cycle 1 students with average grade is 60, increase in cycle 2 with average grade of 80 so it can be concluded that the cooperative learning type Think Pair Share with Words Stick media can be used as a learning strategy for student with learning dissabilities in the first graders because it proved successful in improving building outcomes a sentence.   Keywords: Arranging Sentence, Think Pair Share